Safety, Immunogenicity, and Effectiveness of Defective Viral Particles Arising in Mast Cells Against Influenza in Mice - Huo, Caiyun; Tian, Jijing; Cheng, Jinlong; Xiao, Jin; Chen, Mingyong; Zou, Shumei; Tian, Haiyan; Wang, Ming; Sun, Huiling; Hu, Yanxin (Frontiers in Immunology, 2020)
Mast cells play pivotal roles in the pathogenesis of influenza A virus (IAV) infections. Defective viral particles (DPs) often arise during IAV replication, which can interfere with the replication of infectious viruses and stimulate the antiviral response of host cells. Therefore, DPs are expected to have immune-protective functions in clinic. However, the potent immunogenicity and effectiveness of DPs arising in mast cells during IAV replication have not been reported. In the present study, we showed that DPs generated in the human mastocytoma cell line HMC-1 following H1N1 infection were safe to mice after vaccination. Compared with lung adenocarcinoma cells, A549, DPs generated in infected mast cells had much better immunostimulatory activity, enhancing both humoral and cellular immunity of hosts. Notably, they could significantly increase the expression of immune-associated cytokines, especially the IFN-γ. Due to the robust immunogenicity, thus DPs generated in infected mast cells could stimulate the robust protective immune reaction effectively to fight against lethal IAV re-challenge after vaccination, which result in the high survival, decreased lung injury as well as inhibition of viral replication and inflammatory response in lungs. This study is the first to illustrate and explore the safety, immunogenicity and effectiveness of DPs arising in mast cells against influenza as favorable potential vaccination. The results provide insight into the advances of new prophylactic strategies to fight inﬂuenza by focusing on DPs generated in mast cells.